Pre-operative anemia was associated with all-cause mortality in patients with vertebral fracture who underwent percutaneous vertebroplasty - Wu, Yun-Che; Lin, Yu-Hsien; Lin, Yu-Tsung; Wang, Wen-Chien; Chen, Kun-Hui; Pan, Chien-Chou; Wang, Jun-Sing; Lee, Cheng-Hung (Frontiers in Medicine, 2022)
Purpose: We investigated the association between preoperative anemia and long-term all-cause mortality in patients with vertebral fracture who underwent a vertebroplasty. Methods: We retrospectively selected patients who were admitted for vertebroplasty for vertebral compression fracture between 2013 and 2020. Patients who had pathologic fractures or had no assessment of bone mineral density were excluded. Relevant information was collected from electronic medical records. Patients’ survival status was confirmed at the end of March 2021. Cox-proportional hazard models were conducted to examine the effects of anemia (<12 g/dL vs. ≥ 12 g/dL) and preoperative hemoglobin levels (as a continuous variable) on all-cause mortality with multivariate adjustments. Results: A total of 167 patients were analyzed (mean age 75.8 ± 9.3 years, male 25.7%). After a median follow-up duration of 2.1 years, preoperative anemia (hemoglobin <12 g/dL vs. ≥ 12 g/dL) was independently associated with a higher risk of all-cause mortality (hazard ratio 2.762, 95% CI 1.184 to 6.442, p=0.019). An increase in preoperative hemoglobin was associated with a lower risk of all-cause mortality after multivariate adjustment (hazard ratio 0.775, 95% CI 0.606 to 0.991, p=0.042). Conclusion: Preoperative anemia (<12 g/dL) was independently associated with survival outcome among patients with vertebral compression fractures who underwent vertebroplasty. Our findings highlight anemia as a risk factor of long-term mortality in this elderly surgical population.